2000
DOI: 10.1063/1.480693
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the vibrational linewidth and line shape of Raman spectra using the relaxation function. I. Method and application to nitrogen

Abstract: . (2000). Calculation of the vibrational linewidth and line shape of Raman spectra using the relaxation function : I. method and application to nitrogen. Journal of Chemical Physics, 112(3), 1395-1403. DOI: 10.1063/1.480693 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Just last year the same group also calculated line shapes using the full line shape expression ͑rather than assuming motional narrowing͒ and found in some cases modest deviations from the motional narrowing result. 28 Very recently Gayathri and Bagchi 29 used the model and approach of Oxtoby et al 24 to calculate the line shape along the liquid-gas coexistence line, and in the supercritical region along the critical isochore. Their results for the line width are in reasonable agreement with experiment, especially along the coexistence line.…”
Section: Introductionmentioning
confidence: 99%
“…Just last year the same group also calculated line shapes using the full line shape expression ͑rather than assuming motional narrowing͒ and found in some cases modest deviations from the motional narrowing result. 28 Very recently Gayathri and Bagchi 29 used the model and approach of Oxtoby et al 24 to calculate the line shape along the liquid-gas coexistence line, and in the supercritical region along the critical isochore. Their results for the line width are in reasonable agreement with experiment, especially along the coexistence line.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same group calculated spectra using the full Kubo line-shape expression 33 (rather than assuming the extreme-narrowing limit) at several different thermodynamic state points and found in some cases modest deviations from the motional-narrowing result. 20 In a similar vein, two of us (Everitt and Skinner) developed a model for nitrogen with all of the contributions to the frequency fluctuations discussed above, including resonant intermolecular vibrational interactions and vibration-rotation coupling. 21 The and σ parameters of the two-site Lennard-Jones model were assumed to vary linearly with the vibrational coordinate, and the coefficients were adjusted to fit experimental data for the line shift along the liquid-gas coexistence curve.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of theoretical calculations of the isotropic Raman line shape of nitrogen over the past 25 years. The pioneering paper in the field is due to Oxtoby, who showed that one could calculate the line width from a classical molecular dynamics simulation. They considered liquid nitrogen near the normal boiling point (77 K), showed that the line shape is motionally narrowed, and found a line width in quite good agreement with experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation